An Exploratory Study on Linguistic Sexism in Malaysian Secondary School English Literature Textbooks - Syed Shaharuddin, Sharifah Syakila; Abu Hassan, Maznah (2016)
Linguistic differences between men and women have been a widely popular topic for the last 30 years. This paper is concerned with these differences and how they are represented in todays’ current textbooks. The current study is an attempt to investigate if there is an occurrence of linguistic sexism in the English literature textbooks used in a secondary school in the northern region of Malaysia. The study used two literature textbooks that were currently used by form 4 students in the school. The two books, namely, ‘The Poison Tree’ and ‘A Collection of Short Stories, Poems and Drama’ were examine if linguistic sexism occurred by a critical content analysis (CDA) by Fairclough. This study uses the method of content analysis that was presented by Xu (2009). It is based on the following items: 1. External appearance of female/male characters and 2. Personality of male/female characters .The primary focus of this paper is to see whether linguistic sexism occur in the literature textbooks used in the secondary schools in Malaysia. A qualitative analysis based on the preceding criteria found that the males rule over the females in almost every category linguistically.